Loss of STARD7 Triggers Metabolic Reprogramming and Cell Cycle Arrest in Breast Cancer - Ewelina Dondajewska; Paula Allepuz‐Fuster; Chloé Maurizy; Alexandre Hego; Sandra Ormenese; Quentin Lion; Arnaud Blomme; Pierre Close; Arnaud Lavergne; Latifa Karim; Marc Thiry; Ivan Nemazanyy; et al. (Advanced Science)
Abstract Cancer cells adapt their metabolism to support aberrant cell proliferation. However, the functional link between metabolic reprogramming and cell cycle progression remains largely unexplored. Mitochondria rely on the transfer of multiple lipids from the endoplasmic reticulum (ER) to their membranes to be functional. Several mitochondrial‐derived metabolites influence cancer cell proliferation by modulating the epigenome. Here, the loss of STARD7, a lipid transfer protein whose expression is enhanced in breast cancer, is shown to lead a metabolic reprogramming characterized by the accumulation of carnitine derivatives and S‐Adenosyl‐L‐methionine (SAM). Elevated SAM levels cause the increase of H3K27 trimethylation on many gene promoters coding for candidates involved in cell cycle progression. Likewise, STARD7 deficiency triggers cell cycle arrest and impairs ERα‐dependent cell proliferation. Moreover, EGFR signaling is also impaired in triple negative breast cancer cells lacking STARD7, at least due to deregulated EGFR trafficking to lysosomes. Therefore, mitochondria rely on STARD7 to support cell cycle progression in breast cancer.